2022
DOI: 10.36457/gizindo.v45i2.662
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pola Makan Dan Aktivitas Fisik Dengan Obesitas Sentral Pada Usia Lanjut Di Indonesia: Data Riset Kesehatan Dasar

Abstract: The prevalence of central obesity in Indonesia increased from 2013 to 2018. The increased prevalence is related to changes in lifestyle. This study aimed to determine the relationship between dietary patterns and physical activity with central obesity among the elderly in Indonesia. This study used secondary data from the 2018 Basic Health Research (Riskesdas). Our study used a cross-sectional design. The population in this study was individuals aged 60 years and above with a total sample of 74,035. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
1
0
3
Order By: Relevance
“…This finding was consistent with research conducted by Syauqy et al, which showed a significant association between fatty food March 2024 81 consumption and stroke incidence in a population aged ≥45 years, based on the 2018 Riskesdas data analysis in Indonesia. 36 The limitation of the study included its reliance on secondary data, which led to adjustments in sampling criteria and operational definitions, thereby restricting its ability to explore other factors that may have had a significant influence. Furthermore, the selfreported data may contain bias, especially in recalling past medical history and lifestyle behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with research conducted by Syauqy et al, which showed a significant association between fatty food March 2024 81 consumption and stroke incidence in a population aged ≥45 years, based on the 2018 Riskesdas data analysis in Indonesia. 36 The limitation of the study included its reliance on secondary data, which led to adjustments in sampling criteria and operational definitions, thereby restricting its ability to explore other factors that may have had a significant influence. Furthermore, the selfreported data may contain bias, especially in recalling past medical history and lifestyle behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Perilaku merokok dibagi menjadi dua yaitu merokok (merokok setiap hari atau kadangkadang selama sebulan-terakhir ataupun memiliki riwayat merokok di masa lalu) dan tidak merokok (tidak pernah merokok hingga saat pengumpulan data). 5,19 Data pola makan diperoleh menggunakan food frequency questionnaire (FFQ) yang sudah divalidasi selama 3 bulan terakhir dan dibantu menggunakan food models. 5 Pola makan diukur berdasarkan frekuensi dan porsi konsumsi pada subjek dengan menghitung jumlah hari konsumsi dan porsi dalam sehari.…”
Section: Metode Penelitianunclassified
“…Insulin adalah hormon yang mengatur glukosa dalam darah. Gangguan produksi insulin disertai dengan komplikasi organ, terutama pankreas, dan dieksresikan dengan peningkatan kadar gula darah (Dewi, 2013) Gejala DM jangka panjang adalah dapat menyebabkan berbagai komplikasi mikro dan makrovaskular (Brachmachari, 2011). Yaitu dapat merusak jaringan tubuh lainnya.…”
Section: Aunclassified